ANALISIS MAKNA REFERENSIAL PADA RUBRIK PENDIDIKAN DALAM SURAT KABAR JAMBI EKSPRES EDISI BULAN MARET 2017 - Reski Kurniawan; Sumiharti Sumiharti; Firman Tara (Universitas Batanghari, 2018)
This research is aimed at describing the meaning and total meaning of referential meaning that is used in educational rubric in the newspaper Jambi EkspresMarch edition 2017. This research is qualitatve descriptive. The function of this method is to simplify and to solve things with empiric evidence. The subject of this research is education rubric which is taken randomly by using simple random sampling. The data is collected by using libarary study and documentation technique. The data is analyzed by using steps, they are data reduction, data serving, data triangulation, and conclusion. The result of the analysis shows that there 14 quotes of referential meaning in the education rubric in Jambi Ekspresnewspaper March 2017 edition. .Key Words: referential meaning, education rubric, jambi ekspress